2023
DOI: 10.18063/ijb.740
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional bioprinting of artificial blood vessel: Process, bioinks, and challenges

Abstract: The coronary artery bypass grafting is a main treatment for restoring the blood supply to the ischemic site by bypassing the narrow part, thereby improving the heart function of the patients. Autologous blood vessels are preferred in coronary artery bypass grafting, but their availability is often limited by due to the underlying disease. Thus, tissue-engineered vascular grafts that are devoid of thrombosis and have mechanical properties comparable to those of natural vessels are urgently required for clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 194 publications
0
4
0
Order By: Relevance
“…High UCRScore significantly increases inflammation, stromal, and inflammatory microenvironment scores, which is consistent with inflammatory cells, environmental infiltration, and a series of activated immune-related pathways in the early occurrence of UC [ 40 ]. Clinical cytoplasmic proteins secreted by activated neutrophils, including fecal calcium protegerin and fecal lactoferrin, are used as diagnostic biomarkers of IBD, which is consistent with the increased activity of high UCRScore in neutrophils and Th1 cells [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 95%
“…High UCRScore significantly increases inflammation, stromal, and inflammatory microenvironment scores, which is consistent with inflammatory cells, environmental infiltration, and a series of activated immune-related pathways in the early occurrence of UC [ 40 ]. Clinical cytoplasmic proteins secreted by activated neutrophils, including fecal calcium protegerin and fecal lactoferrin, are used as diagnostic biomarkers of IBD, which is consistent with the increased activity of high UCRScore in neutrophils and Th1 cells [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 95%
“…Type2 was significantly enriched in immunoinflammatory pathways, with a high CRDscore, high immune activation, and low level of collagen metabolism. Recent research has shown that inflammation plays a key role in coronary artery disease and atherosclerosis, in which immune mechanisms interact with metabolic risk factors www.nature.com/scientificreports/ to initiate, propagate, and activate lesions in the arterial branch 46,47 . Immune cells dominate early atherosclerotic lesions, their effector molecules accelerate the progression of the lesions, and activation of inflammation can elicit acute coronary syndromes [48][49][50] .…”
Section: Discussionmentioning
confidence: 99%
“…Bioprinting of functional tissues such as myocardium is a complex phenomenon due to their complex anatomical structures, thus in vitro fabrication of myocardial tissues requires an arrangement of multiple cell types in order, including vascular network, lymphatic vessels and muscle tissues, within engineered cardiac construct tissues [ 42 ]. As the ultimate goal in 3D bioprinting is to print the injured or damaged organ in situ, attention should be paid to the sterilization and safety of the in situ bioprinting processes [ 170 ].…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%